Protective Effect of Lyophilization on Fermentative, Microbiological and Sensory Properties of Kefir - Moretti, Ana Florencia (2019)
Kefir is a fermented beverage produced from kefir starter, by means of the milk fermentation with kefir grains. These grains are a protein and polysaccharide matrix that contains Lactic Acid Bacteria (LAB), Acetic Acid Bacteria (BAA) and yeasts. This study aimed to assess the protective activity of the lyophilization process on the activity of kefir grains by comparing their microbiological composition, sensory characteristics and antimicrobial effect on fermented products obtained either from lyophilized and fresh kefir grains. Acidification kinetics and microbial counts were performed on fermented milks obtained from fresh or freeze-dried grains. Inhibitory activity tests against Escherichia coli and Salmonella enterica serovar Enteritidis were carried out with different dilutions of cell free supernatants from fermented milks. On the other hand, similarity and acceptability tests were performed to compare the sensory characteristics of fermented milks obtained from fresh and freeze-dried grains. The microbiological composition and acidification capability of the freeze-dried grains were stable until 6 months of storage at 4°C. Moreover, the minimum inhibitory concentration of fresh and freeze-dried grains was similar (20% v/v) for both pathogens. Additionally, the sensory panel did not detect differences between milk fermented with fresh or freeze-dried kefir grains; the kefir beverage obtained from the freeze-dried kefir grains fermentation showed a wide sensory acceptance among the population surveyed. We considered that lyophilization followed by the storage conditions applied were suitable for the survival of the kefir micro biota, the sensory characteristics and the antimicrobial capability of the fermented beverage after an adequate reactivation process of the grains. In conclusion, the reactivation process risk management is an important stage to ensure a suitable carriage and therefore maximize the kefir grains for large scale use.